Hamamelitannin Analogues that Modulate Quorum Sensing as Potentiators of Antibiotics against Staphylococcus aureus. (20th April 2016) - Vermote, Arno; Brackman, Gilles; Risseeuw, Martijn D. P.; Vanhoutte, Bieke; Cos, Paul; Van Hecke, Kristof; Breyne, Koen; Meyer, Evelyne; Coenye, Tom; Van Calenbergh, Serge
Abstract: The modulation of bacterial communication to potentiate the effect of existing antimicrobial drugs is a promising alternative to the development of novel antibiotics. In the present study, we synthesized 58 analogues of hamamelitannin (HAM), a quorum sensing inhibitor and antimicrobial potentiator. These efforts resulted in the identification of an analogue that increases the susceptibility of Staphylococcus aureus towards antibiotics in vitro, in Caenorhabditis elegans, and in a mouse mammary gland infection model, without showing cytotoxicity.